A method for evaluating paleo hydrocarbon pools and predicting secondary reservoirs: a case study of the Sangonghe Formation in the Mosuowan area, Junggar Basin - Wei-Jiao Ma; Yan-Zhao Wei; Shi-Zhen Tao (Petroleum Science, 2018)
Abstract Taking the Jurassic Sangonghe Formation in the Mosuowan-Mobei area of the Junggar Basin as an example, this paper provides a method that evaluates paleo hydrocarbon pools and predicts secondary reservoirs. Through Quantitative Grain Fluorescence (QGF) experiments, well-tie seismic correlation, and paleo structure analysis, the scale and distribution of paleo hydrocarbon pools in the study area are outlined. Combining current structural features and fault characteristics, the re-migration pathways of paleo oil and gas are depicted. Based on barrier conditions on the oil re-migration pathways and current reservoir distribution, we recognize three types of secondary reservoirs. By analyzing structural evolution and sand body-fault distribution, the major control factors of secondary reservoirs are specified and, consequently, favorable zones for secondary reservoirs are predicted. The results are mainly as follows. (1) In the primary accumulation period in the Cretaceous, paleo hydrocarbon pools were formed in the Sangonghe Formation of the Mosuowan uplift and their size and distribution were extensive and the exploration potential for secondary reservoirs should not be ignored. Besides, paleo reservoirs were also formed in the Mobei uplift, but just small scale. (2) In the adjustment period in the Neogene, traps were reshaped or destroyed and so were the paleo reservoirs, resulting in oil release. The released oil migrated linearly northward along the structural highs of the Mobei uplift and the Qianshao low-relief uplift and then formed secondary reservoirs when it met new traps. In this process, a structural ridge cooperated with sand bodies and faults, applying unobstructed pathways for oil and gas re-migration. (3) The secondary hydrocarbon pools are classified into three types: low-relief anticlinal type, lithologic pinch-out type and fault block type. The distribution of the first type is controlled by a residual low uplift in the north flank of the paleo-anticline. The second type is distributed in the lithologic pinch-out zones on the periphery of the inherited paleo uplift. The third type is controlled by fault zones of which the strikes are perpendicular to the hydrocarbon re-migration pathways. (4) Four favorable zones for secondary reservoirs are predicted: the low-relief structural zone of the north flank of the Mosuowan paleo-anticline, the fault barrier zone on the western flank of the Mobei uplift, the Qianshao low-relief uplift and the north area of the Mobei uplift that parallels the fault zone. The study above effectively supports the exploration of the Qianshao low-relief uplift, with commercial oil discovered in the Qianshao1 well. Besides, the research process in this paper can also be applied to other basins to explore for secondary reservoirs.